Islam in Victorian Britain : the life and times of Abdullah Quilliam - Geaves, Ron (Kube Publishing, 2010)
An entertaining biography of Victorian Britain's most notable Muslim, Abdullah Quilliam, the Sheikh of Islam of the British Isles.